2021
DOI: 10.31326/jisa.v4i2.922
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of Gold Price Movement by Comparing Naive Bayes, Support Vector Machine, and K-NN

Abstract: Gold is a yellow precious metal that can be forged so it is easy to form with various forms of jewelry such as pendants, earrings, rings, bracelets and others, gold has a high value. Gold itself is an exchange rate used in ancient times before the existence of money as it is today. Gold also can be used as an investment that is profitable for the investor and it has less risks. Investment is a form of fund management to give benefit by putting fund in allocation that is predicted will give additional benetifs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The comparative analysis research result on the classification of heart disease using the K-NN, Naive Bayes, and SVM algorithms shows that the SVM algorithm performs better than the other algorithms, with 92% accuracy; while the Naive Bayes performance is the worst with 88% [33]. In the performance comparison of predicting gold price movements, the K-NN algorithm performs better than other algorithms, with an accuracy of 61.9% [34]. The comparison of the Naïve Bayes, K-NN, and SVM algorithms in social media sentiment classification, shows that the Naive Bayes algorithm yields the highest performance with an accuracy of 79.8%, better than the K-NN (50.23%), and SVM (75.29%) algorithms [35].…”
Section: E Cross-validation Evaluationmentioning
confidence: 98%
“…The comparative analysis research result on the classification of heart disease using the K-NN, Naive Bayes, and SVM algorithms shows that the SVM algorithm performs better than the other algorithms, with 92% accuracy; while the Naive Bayes performance is the worst with 88% [33]. In the performance comparison of predicting gold price movements, the K-NN algorithm performs better than other algorithms, with an accuracy of 61.9% [34]. The comparison of the Naïve Bayes, K-NN, and SVM algorithms in social media sentiment classification, shows that the Naive Bayes algorithm yields the highest performance with an accuracy of 79.8%, better than the K-NN (50.23%), and SVM (75.29%) algorithms [35].…”
Section: E Cross-validation Evaluationmentioning
confidence: 98%
“…Yahya Suryana and Tjong Wan Sen also conducted research on gold price movement by comparing 3 methods namely Naive Bayes, Support Vector Machine, and K-Nearest Neighbor. By the three methods, it was found that KNN had the best accuracy, namely 61.9%, then SVM with an accuracy of 57.5%, and finally, Naive Bayes had the lowest accuracy, namely 55.5% [11].…”
Section: Introductionmentioning
confidence: 99%
“…It presents the outcomes of a forecasting process capable of creating models and predictions using historical data. Additionally, there is an article that conducts a comparison between Naive Bayes, support vector machine, and K-NN methods for forecasting fluctuations in gold prices, specifically within the realm of gold stock investment (Suryana and Sen, 2021).…”
Section: A Introductionmentioning
confidence: 99%